COVID-19 Pandemic: Experiences of People with Visual Impairment - María del Pilar Oviedo-Cáceres; Karen Natalia Arias-Pineda; María del Rosario Yepes-Camacho; Patricia Montoya Falla (Universidad de Antioquia, 2021)
Objective. To understand changes in daily life emerging from the COVID-19 Pandemic in people with visual impairment from four cities of Colombia. Methods. Exploratory-type, descriptive qualitative study. The study conducted 26 semi-structured interviews via telephone. The analysis process used the methodological design from the approach proposed by Taylor and Bogdan: following the discovery process, coding and relativizing of data. Results. Three categories emerge: 1) Transformations in daily dynamics, 2) Barriers to mobility, and 3) Use of technology. Conclusion. People with visual impairment report barriers to mobility to take public transportation, which can affect maintenance of their autonomy and independence. Using technological tools is identified as facilitators for the continuity of educational and work activities; however, some did not have computer literacy or the basic inputs for connectivity. Difficulties were identified to continue work activities and maintain income.